Effect of Application of Endophytic Bacteria on the Development of Bacterial Leaf Blight Disease, Growth, and Production of Rice Plants - Marwan, Husda; Hayati, Islah; Defitri, Yuza (Universitas Medan Area, 2023)
Bacterial leaf blight can be found in various stages of rice plant growth, so this disease can affect the growth and production of rice plants. This research aims to determine the effect of applying an endophytic bacterial formula to rice seedlings on the development of HDB disease, growth, and production of rice plants. This study used 4 isolates of endophytic bacteria (isolates BE-KH1, BE-M2, BE-M3, and BE-S5) which were formulated in coconut water waste + peptone. The results of the study showed that the application of the endophytic bacterial formula to rice seedlings was able to reduce the severity of bacterial leaf blight by 54,5 – 63,2% and had an effect on growth, full grain weight, and rice grain weight in rice plants inoculated with Xanthomonas oryzae pv. oryzae bacteria.